Determination of stability of cryptographic protocols on the basis of their probabilistic models - Заячук, Ярослав Іванович; Мойсеєнко, Олена Володимирівна; Толстокоров, Андрій Петрович (Eastern-European Journal of Enterprise Technologies, 2011)
The article discusses the probabilistic models of cryptography zero-knowledge protocols